Comparison of Debonding of Different Composite Resin Bonds and Acrylic Tooth with Acrylic Denture Base after Thermocycling Regimes. - Aso M. Zangana; Ghalib R. Hawrami; Samir A. Hamad (Erbil Dental Journal)
Background and objectives: The purpose of this study was to repair detached acrylic tooth using composite resin and comparing it debonding with cold cure acrylic after thermocycilg process.